Respuesta :

Answer:

  x = 1

Step-by-step explanation:

To find a solution to this by graphing, you would typically make a graph of the expression on the left, and another graph of the expression on the right. Where they intersect is the solution.

You would graph ...

  • y = 2x
  • y = -x +3

You're only interested in the x-value where these lines cross, x=1.

_____

Alternate method

Graph the difference of the left side and the right side:

  y = (2x) -(-x +3)

and look for the value of x that makes y = 0. This, too, gives the solution x=1.

__

Of course, once you have the equation ...

  0 = 3x -3

the solution is pretty obvious. (Divide by 3 to make it more obvious.)

Ver imagen sqdancefan
Ver imagen sqdancefan
ACCESS MORE